Biomass-derived cobalt/carbon hierarchically structured composites for efficient oxygen electrocatalysis and zinc–air batteries. Issue 13 (6th June 2022) - Chen, Jing; Yang, Shaoxuan; Zhang, Zhengping; Wang, Feng
Abstract : In this work, we constructed a biomass-derived composite (denoted as Co@Co–N, S–C), which exhibited excellent efficient bifunctional performance for ORR/OER, as well as an outstanding performance when employed in secondary zinc–air batteries. Abstract : Rechargeable zinc–air batteries with low-cost and highly active bifunctional electrocatalysts have aroused extensive research interests. Herein, a hierarchically structured electrocatalyst was synthesized from biological waste (bovine serum albumin, BSA), integrating encapsulated Co nanoparticles and Co–N–C moieties. The obtained electrocatalysts exhibited superior activities for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), providing a small potential gap (Δ E ) of 0.74 V between the ORR half-wave potential and the OER potential at 10 mA cm −2 . Furthermore, the aqueous and flexible quasi-solid-state zinc–air batteries assembled with these hierarchically structured composites demonstrated excellent electrochemical performance with maximum power densities of 173.7 mW cm −2 and 79.6 mW cm −2, as well as long-term cycling stability. This integrated strategy opens up an effective way for the development of novel nanostructured electrocatalysts from biological waste.